1980
DOI: 10.1002/crat.19800151103
|View full text |Cite
|
Sign up to set email alerts
|

The precipitation of sparingly‐soluble acid, neutral and basic metal salts from aqueous solution: Ionic equilibria at different pHs, precipitate phases and precipitation mechanisms

Abstract: The precipitations of the sparingly-soluble acid, neutral and basic salts of the divalent cations beryllium, magnesium, calcium, strontium, barium, manganese (11), iron (11), cobalt (11), nickel (II), copper (11), zinc, cadmium, mercury (11), tin (11) and lead (11) with the inorganic anions sulphate, chromate, molybdate, monohydrogen phosphate, phosphate, and carbonate (from supersaturated aqueous solutions) are surveyed. The different types of ionic equilibria (cation hydrolysis, anion hydrolysis, ion-pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…It can be found that the bands at 1472 and 730 cm −1 disappear, as the temperature increases to melting point, which is in accordance with the reports in literature 12, 22. Thus, these two bands belong to the infrared crystalline bands, related to the orthorhombic modification of HDPE 12, 22, 33–35…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It can be found that the bands at 1472 and 730 cm −1 disappear, as the temperature increases to melting point, which is in accordance with the reports in literature 12, 22. Thus, these two bands belong to the infrared crystalline bands, related to the orthorhombic modification of HDPE 12, 22, 33–35…”
Section: Resultssupporting
confidence: 91%
“…In the meantime, the band at 719 cm −1 splits into two bands at 730 and 719 cm −1 . This fact demonstrates that HDPE sample begins to crystallize at 107°C,12, 22, 33–35 which is in agreement with the DSC measurement in Figure 1(b).…”
Section: Resultssupporting
confidence: 89%
“…Thus, it is proposed that the first mechanistic step involves an acid/base reaction between solution protons and the electrode surface. The p K a of the surface oxide is reported to be approximately 7.7 . Notably, when electrolysis experiments are performed at pH values higher than this pH, no formate production is observed, supporting the notion that protonation of the surface is important.…”
Section: Resultsmentioning
confidence: 77%
“…The pK a of the surface oxide is reported to be approximately 7.7. 38 Notably, when electrolysis experiments are performed at pH values higher than this pH, no formate production is observed, supporting the notion that protonation of the surface is important.…”
Section: Electrochemical Behavior Of Lead and Bismuthmentioning
confidence: 68%